Optimalisasi Lahan Untuk Pengembangan Rekreasi dan Budaya dengan Metode Highest and Best Use (HBU) - Priambudi, Bagus Nuari; Haryanto, Ragil (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
Since 2010 the bussines property development in Semarang City has significant increased. This was shown by skylines likes mall, office complexs and also hotel. On the other side the availability of the land in the city is limit. Owing to that It needs land use optimalization. Oe way is a bussines property with the purpose is to maximalized the land managing so by that the land will got a high cost. The aim of the research was to know the optimalized of land used with used Highest and Best Use Method (HBU) and to get the public opinion related with the developed. The Research method was mixed method (Quantitative and Qualitative) and the locations were Taman Budaya Raden Saleh (TBRS) and Wonderia. The wide of thus areas were 90.000 m2 or 9 Ha. Thus was choosed by Trans Retail Property. The reseason was because the areas were strategic and width lands. On the other hand the attraction that are showed in thus recreations were not attractive. By thus fact it can be say that the land used of the two areas were not yet optimal.By the analized it can be concluded that by the investment approach : the complexs of Taman Budaya Raden Saleh and Wonderia feasible and allow to develop hotel and mall with the high profit. Beside that it also can get benefit of social economic it needs redesain of the city forest used (existing) without any loosing their functions. By that it hopes can get balancing between private public and best and also highest land used in the complexs of Taman Budaya Raden Saleh and Wonderia.